Use of special knowledge in proving criminal proceedings - Бишевець, О.В. (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2015)
Based on an analysis of scientific literature and practical materials, this article examines the essence and concept of special knowledge. It cites publications that initiated research into this concept. The author describes existing scientific approaches to understanding the concept of special knowledge, points out their shortcomings, and attempts to provide her own definition. The article pays special attention to the forms of application of special knowledge in the investigation of crimes. It is determined that, to date, there is no single systematization of the forms of application of special knowledge. Although science denies the validity of distinguishing between procedural and non-procedural forms of application of special knowledge, in the author's opinion, such a systematization deserves to exist. Keywords: criminal proceedings, evidence, special knowledge, forms of use of special knowledge, forensic examination.

У статті на основі аналізу наукової літератури і матеріалів практики досліджено сутність та поняття спеціальних знань. Вказано публікації, які започаткували дослідження цього поняття. Автор описала існуючі в науці підходи до розуміння поняття спеціальних знань, вказала на їх недоліки і здійснила спробу дати йому своє визначення. Окрему увагу в статті приділено формам застосування спеціальних знань в ході розслідування злочинів. Визначено, що на сьогоднішній день відсутня єдина систематизація форм застосування спеціальних знань. Хоча в науці заперечують обґрунтованість виділення серед форм застосування спеціальних знань таких, як процесуальна і не процесуальна, на думку автора, така систематизація заслуговує на існування. Ключові слова: кримінальне провадження, доказування, спеціальні знання, форми використання спеціальних знань, судова експертиза.
Використання спеціальних знань у доказуванні в кримінальних провадженнях